228Ra and 226Ra measurement on a BaSO4 co-precipitation source. (January 2015) - Medley, Peter; Martin, Paul; Bollhöfer, Andreas; Parry, David
Abstract: One of the most commonly-used methods for determination of 226 Ra, particularly in water samples, utilises co-precipitation of Ra with BaSO4, followed by microfiltration to produce a source for alpha counting. This paper describes two extensions to BaSO4 co-precipitation methods which enable determination of 228 Ra using the same source. The adaptations presented here do not introduce any contaminants that will affect the separation of radium or alpha counting for 226 Ra, and can be used for re-analysis of already existing sources prepared by BaSO4 co-precipitation. The first adaptation uses detection of 228 Ac on the source by gamma spectrometry. The detection efficiency is high, allowing analysis of water samples at sufficiently low activity to be suitable in testing for compliance with drinking water quality standards. As 228 Ac grows in quickly, taking less than 2 days to reach equilibrium with the 228 Ra parent, this can also be useful in radiological emergency response situations. The second adaptation incorporates a method for the digestion of BaSO4 sources, allowing separation of thorium and subsequent determination of 228 Th activity. Although ingrowth periods for 228 Th can be lengthy, very low detection limits for 228 Ra can be achieved with this technique. Highlights: We developed two methods for 228 Ra measurement on Ba(Ra)SO4 co-precipitation sources. Measurement by gamma spectrometry using the daughter 228 Ac is rapid. Detection limits are suitable for assessment of drinking water quality. The second approach uses alpha spectrometry on a separated Th fraction. This is more sensitive than gamma spectrometry after an ingrowth period greater than about 1 month.